Economics, Ecology, and the Roots of Western Faith: Perspectives from the Garden - Gottfried, Robert R. (Rowman & Littlefield Publishers, 1995)
Environmentalists have turned to Eastern religion, Deep Ecology and Native American religion for alternatives to the Western view that humans should dominate nature. In Economics, Ecology, and the Roots of Western Faith, Robert R. Gottfried persuasively demonstrates that the ancient Hebrew worldview, found in the Torah and the New Testament, is remarkably 'green.' Drawing on these insights from ancient Western thought and economic understanding of ecosystems and natural processess, Gottfried analyzes the prerequisites for maintaining or improving human welfare and ecological vitality in terms of land economics and management.